The Role of Acromioplasty for Management of Rotator Cuff Problems: Where Is the Evidence? - Lewis L. Shi; T. Bradley Edwards (Advances in Orthopedics)
The incidence of acromioplasty has increased dramatically in recent decades, but its role in rotator cuff surgery has been debated. Neer popularized the extrinsic theory of rotator cuff pathology, where mechanical compression of the coracoacromial arch leads to tearing of the rotator cuff. Under this theory, acromioplasty is advocated to modify acromial morphology as an essential part of rotator cuff surgery. Proponents of the intrinsic theory suggest rotator cuff tendons undergo degeneration through aging and overuse, and that bursectomy alone without acromioplasty is sufficient. There exist cadaveric studies, expert opinions, and numerous case series espousing both sides of the argument. Recently, however, numerous high-quality prospective randomized controlled trials have been published examining the role of acromioplasty. They have similar study design and randomization protocols, including groups of arthroscopic rotator cuff repair with bursectomy and acromioplasty versus isolated bursectomy. The results have been consistent across all studies, with no difference in the outcomes of the acromioplasty and isolated bursectomy groups. Current evidence does not support the routine use of acromioplasty in the treatment of rotator cuff disease.